The James Webb Space Telescope - a new era in astronomy - Coelho, Jaziel G. (Cadernos de Astronomia, 2022)
The James Webb Space Telescope (JWST) is a 6.5 m infrared space telescope launched on December 25, 2021. Since its launch and with the release of the first calibration images, the JWST has already impacted us enormously. Months later, on July 12, 2022, the world was amazed to receive the first color images of this new window of observation of the cosmos. In this and the coming decades, the JWST will impact all fields of astrophysics. Equipped with four unique science instruments, providing a wide range of imaging and spectroscopic capabilities covering the 0.6 to 28 micron wavelength range, the JWST will provide unprecedented sensitivity to probe the early Universe, understand the origin and evolution of galaxies, those that emerged just a few hundred million years after the Big Bang. JWST will study star formation, black holes, dark matter, protoplanetary systems, exoplanets and the origin of life. This article provides a brief overview of the JWST mission. Two decades after starting the development of this powerful space observatory through an international partnership led by the United States, in collaboration with Europe and Canada, the JWST's core science mission ushers in a new era of astronomy. In addition, the JWST is a landmark mission that will guide the development of future international space observatories as well as giant ground-based telescopes.
Keywords: James Webb; infrared astronomy; galaxies; universe